Dynamics of social integration among the Indian migrant community in Sabah - Mohd Juhar Harun; Jane Wong Kong Ling; Nordiana Nasuha Molinka; Jasman Bandar; Sharifah Yong Nadia Omar Salleh (Human Resource Management Academic Research Society (HRMARS), 2025)
This study explores the practice of interethnic marriage between the Indian community and local ethnic groups in Sabah within the historical context of migration under the administration of the British North Borneo Chartered Company (BNBCC). Employing a historical methodology, the research traces the phased and systematic migration of Indians to Sabah and examines its impact on the region’s social structure. This migration gave rise to a significant phenomenon of social integration, as evidenced by the emergence of mixed Indian-local ethnic communities. These intermarriages reflect a process of assimilation between majority and minority ethnic groups, contributing to the social dynamics of Sabah. The paper is structured into three main sections: the first discusses the background and early migration of Indians to Sabah under the BNBCC; the second identifies key factors that encouraged interethnic marriages between Indians and local communities; and the third analyses the impact of such marriages on the formation of hybrid identities. Understanding the history of Indian migration is crucial in examining the broader process of social integration involving the Indian community in Sabah.